(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2023)
The study aimed to know the reality of the practice for administrative transparency in the Syrian Ministry of Education from the point of view of its employees in accordance with the variables (Gender, years of service, scientific qualification). The study followed the descriptive analytical curriculum and the sample of the study consisted of 285 workers in the Directorate of Education. The resolution was used to collect data and consisted of 25 items. The study reached a set of results, the most important of which are: - There are statistically significant differences between the averages of the respondents to the questionnaire of the reality of the practice for administrative transparency due to the gender variable in favor of females. -There are statistically significant differences between the averages of respondents to the questionnaire of the reality of the practice for administrative transparency due to the change in years of experience in favor of less than 5 years. -There are statistically significant differences between the averages of respondents to the questionnaire of the reality of the practice for administrative transparency due to the change in scientific qualification in favor of graduate studies.